New discoveries for the subfamily Phtisicinae Vassilenko, 1968 (Crustacea: Senticaudata) from the Brazilian coast - Mauro, Fábio da Motta; Nascimento, Priscila Soares do; Serejo, Cristiana Silveira (European Journal of Taxonomy, 2020)
Amphipod material collected from Brazil on Ilha do Arvoredo, (Santa Catarina), Campos Basin, (Rio de Janeiro) and Espírito Santo Basin (Espírito Santo) in the southwestern Atlantic Ocean yielded new taxonomic findings for the subfamily Phtisicinae Vassilenko, 1968. Hemiproto wigleyi McCain, 1968, previously recorded from the Gulf of Mexico to the Caribbean Sea, is herein redescribed and recorded for the first time from the Brazilian coast. The type material of Phtisica verae Quitete, 1979, a poorly described species recorded from Brazil and based only on its original description, was examined and considered herein as a junior synonym of P. marina Slabber, 1769, a well-known and widely distributed species from the Atlantic Ocean and the Mediterranean Sea. In this paper, Phtisica marina is redescribed, with its two morphotypes of male gnathopod two, and compared with previous descriptions. The geographic distribution of both H. wigleyi and P. marina is provided.